Factors Related To The Coverage Of Tetanus Toxoid Immunization For Pregnant Women - Andi Nurlaily; Kurniati, Ely (Jurnal Life Birth, 2018)
Coverage of TT immunization for pregnant women, the number of pregnant women was 437 while coverage of TT 1 immunization was 122 (54.7%), TT2 immunization 63 (7.2%). In January-September 2016 the number of pregnant women was 380 while the coverage of TT 1 immunization was 85 (9.0%) people, TT2 was 32 (4.3%) people. In November 2016 January 2017 the number of pregnant women was 114 while the coverage of TT 1 immunization was 26 (3.8%) people, TT2 was 17 (2.0%). This could be interpreted that the TT immunization coverage was not following which is expected. The purpose of this study was to determine the relationship of factors related to the coverage of tetanus toxoid immunization for pregnant women. Observational analytic study design with a cross-sectional approach. The population in this study amounted to 114 people and a sample of 53 pregnant women with sampling using the technique. Consecutive sampling. The results of the study there is a relationship between knowledge about coverage of tetanus toxoid immunization for pregnant women with a p-value of 0.022, there is no relationship between attitude and coverage of tetanus toxoid immunization for pregnant women at Bonto Tiro Health Center in 2017 with the results of p-value 1,000, there is a relationship between education with coverage of tetanus toxoid immunization for pregnant women at Bonto Tiro Health Center in 2017 with a p-value of 0.002, there is no relationship between work and coverage of tetanus toxoid immunization for pregnant women at Bonto Tiro Health Center in 2017 with results p-value 0.556, there is no relationship between family support and coverage of tetanus toxoid immunization for pregnant women at the Bonto Tiro Health Center in 2017 with a p-value of 1,000.